Effects of Z-value on physicochemical and biological properties of β-SiAlONs ceramics. Issue 24 (15th December 2021) - Zhang, Liguo; Zhang, Can; Ji, Yun; Xu, Enxia; Mu, Jinghua; Liu, Xinhong; Zhao, Fei; Yuan, Huiyu; Cui, Junyan; Gao, Jinxing
Abstract: This study evaluated the effects of different Z-values on the physical, chemical, and biological properties of β-SiAlON ceramics. Increasing the Z-value of the β-Si3 N4 solid solution's main phase resulted in the replacement of Si–N bonds with Al–O bonds. The number of columnar crystals decreased, bulk density increased, and porosity decreased, thus transforming the fine-particle microstructure of β-Si3 N4 into the columnar structure of β-SiAlON. The compressive strength increased, which facilitated sintering at 1500 °C without sintering auxiliaries. H + and OH − ions in deionized water broke the covalent bonds on the β-SiAlON surface, thereby forming new Si–OH, Al–OH, and N–H bonds on the β-SiAlON surface and producing SiO4 4−, AlO2 −, and NH4 + groups in the solution. Increasing the soaking time changed the compositions of ionized H + and OH − ions, thus increasing the pH. MC3T3-E1 cells were cultured on the β-SiAlON surface, and it was observed that the increase in the Z-value of β-SiAlON had no influence on cell adhesion and spreading, but it may slightly suppress cell proliferation at high Z-values. At low Z-values, the low AlO2 − concentration helps promote osteogenic differentiation and mineralized nodule formation. Thus, β-SiAlON ceramics possess excellent physical, chemical, and biological properties and are considered excellent bone-repairing materials.